Implementation Of Legitimacy Theory On SME To Achieve Sustainability - Dewi Diah Fakhriyyah; Sudarmiatin Sudarmiatin; Agus Hermawan (Cita konsultindo, 2023)
Small and Medium Enterprise (SME) have and important role to contribute to the national economy and also can contribute to achieve sustainable development goals (SDG). To achieve sustainability, SME should have a positive effect on the surrounding community. There is a theory that can be applied to support the existence of SMEs, namely the legitimacy theory. Legitimacy theory is widely used in the literature to explain Corporate Sustainability. Some of the things that SMEs do to achieve legitimacy are as follows, SME implement corporate social responsibility, communicating CSR to stakeholder, attract foreign investor by enhance social, environment, and governance performance. In addition, the legitimacy of SME can be viewed from the owner-manager of SME’s perspective. Based on owner manager’s perspective, to establish legitimacy can be from customer’s satisfaction through the value of the product/service, and also by give a responsibility to employees. SMEs that can achieve legitimacy, can achieve sustainability.